How to build a resilient monetary union? Lessons from the euro crisis - Grégory Claeys (Asian Development Bank Institute (ADBI), 2017)
This paper describes the institutional flaws that led to the euro crisis, assesses the institutional reforms that were put in place during and in the aftermath of the crisis, and evaluates the remaining fragilities of the architecture of the European monetary union. In mid-2017, growth in the euro area appears to be finally picking up after 10 years of recessions and slow recoveries. European leaders should not be complacent and wait for the next crisis to complete the single currency architecture. On the contrary, these quieter times offer a good occasion to reflect on the future of euro-area institutions and to build a more permanent setup than that implemented in the heat of the crisis. In order to achieve a more resilient monetary union in Europe, we propose: to complete the banking union as soon as possible; to promote a really ambitious capital market union able to provide real risk sharing between member states of the monetary union; to reform the use of macroprudential tools and make their use more systematic in order to avoid divergence between countries in financial cycles; and most importantly to improve the defective macroeconomic policy framework to avoid a repeat of the policy mistakes of recent years.
Keywords: E61; E62; E63; H77; 330; economic governance; European Union; macroeconomic policy; stabilization mechanisms